2002
DOI: 10.1105/tpc.002907
|View full text |Cite
|
Sign up to set email alerts
|

Discrete Forms of Amylose Are Synthesized by Isoforms of GBSSI in Pea[W]

Abstract: Amyloses with distinct molecular masses are found in the starch of pea embryos compared with the starch of pea leaves. In pea embryos, a granule-bound starch synthase protein (GBSSIa) is required for the synthesis of a significant portion of the amylose. However, this protein seems to be insignificant in the synthesis of amylose in pea leaves. cDNA clones encoding a second isoform of GBSSI, GBSSIb, have been isolated from pea leaves. Comparison of GBSSIa and GBSSIb activities shows them to have distinct proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 68 publications
2
40
0
Order By: Relevance
“…In waxy rice, while endosperm starch does not contain amylose, the starch fractions in the embryo, leaf blades, stems, and roots do contain amylose (Blakeney and Matheson 1984). Recent research has identified a new GBSS, designated GBSSII, in waxy wheat and amf pea, which is responsible for amylose synthesis in non-storage tissues Nakamura et al 1998;Vrinten and Nakamura 2000;Edwards et al 2002). Scheible et al (1997) reported that in tobacco, nitrate could be a signal that regulates starch synthesis by inhibiting the expression of the small subunit of ADPGlc pyrophosphorylase (AGPase) and decreasing the concentration of 3-phosphoglyceric acid (3PGA), the allosteric activator of AGPase.…”
Section: Introductionmentioning
confidence: 98%
“…In waxy rice, while endosperm starch does not contain amylose, the starch fractions in the embryo, leaf blades, stems, and roots do contain amylose (Blakeney and Matheson 1984). Recent research has identified a new GBSS, designated GBSSII, in waxy wheat and amf pea, which is responsible for amylose synthesis in non-storage tissues Nakamura et al 1998;Vrinten and Nakamura 2000;Edwards et al 2002). Scheible et al (1997) reported that in tobacco, nitrate could be a signal that regulates starch synthesis by inhibiting the expression of the small subunit of ADPGlc pyrophosphorylase (AGPase) and decreasing the concentration of 3-phosphoglyceric acid (3PGA), the allosteric activator of AGPase.…”
Section: Introductionmentioning
confidence: 98%
“…The eight conserved regions present in all plant GBSS (Cao et al 1999), were identified. Conserved regions 1 and 8 contain the KTGGL motif, which is considered to be the ADPglucose binding site (Furukawa et al 1993), and the KTGGL look-alike motif (Edwards et al 2002), respectively. The deduced amino acid sequence of the mature CkGBSS polypeptide shared higher identity with those of the GBSS from Chlamydomonas (65%) and Ostreococcus (59%) than with the GBSSI and GBSSII sequences of vascular plants (37-53%) (identities were obtained by BLASTP, in which N-and C-terminal ambiguous alignments were excluded).…”
Section: Amino Acid Sequence Alignment Of Gbss Polypeptidesmentioning
confidence: 99%
“…In these mutants, amylose is not synthesized, and therefore, the starch granules are not stained blue-violet with iodine. Vascular plants have two GBSS isoforms, GBSSI which is involved in amylose synthesis in storage tissues (for review see Smith et al 1997) and GBSSII which is responsible for amylose synthesis in non-storage tissues such as leaves and stems (Denyer et al 1997;Fujita and Taira 1998;Nakamura et al 1998;Vrinten and Nakamura 2000;Edwards et al 2002;Dian et al 2003). …”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that other enzymes contribute to the synthesis of amylose, however GBSS is the only enzyme absolutely required for its synthesis (Ball & Morell 2003). There are separate GBSS genes expressed in endosperm and other parts of the plant providing a basis for observed differences in amylose content and structure between leaf and endosperm starches (Nakamura et al 1998;Edwards et al 2002).…”
Section: Starch Biosynthesis and Functionalitymentioning
confidence: 99%